2017
DOI: 10.1063/1.4984788
|View full text |Cite
|
Sign up to set email alerts
|

Rapid concentration and elution of malarial antigen histidine-rich protein II using solid phase Zn(II) resin in a simple flow-through pipette tip format

Abstract: Rapid diagnostic tests (RDTs) designed to function at the point of care are becoming more prevalent in malaria diagnostics because of their low cost and simplicity. While many of these tests function effectively with high parasite density samples, their poor sensitivity can often lead to misdiagnosis when parasitemia falls below 100 parasites/l. In this study, a flow-through pipette-based column was explored as a cost-effective means to capture and elute more histidine-rich protein II (HRPII) antigen, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“… 16 , 19 In addition, HRP2 in the 43,600 parasites/μL stock was previously determined to be 2.2 pM per parasite/μL. 23 The p LDH concentration of in-house D6 P. falciparum culture (stock 43,600 parasites/μL) was determined to be 4.4 pM per parasite/μL using a standard well-plate ELISA, N = 6 ( Supplemental Text 1 ).…”
Section: Methodsmentioning
confidence: 99%
“… 16 , 19 In addition, HRP2 in the 43,600 parasites/μL stock was previously determined to be 2.2 pM per parasite/μL. 23 The p LDH concentration of in-house D6 P. falciparum culture (stock 43,600 parasites/μL) was determined to be 4.4 pM per parasite/μL using a standard well-plate ELISA, N = 6 ( Supplemental Text 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This field-deployable sample isolation and concentration tool displayed up to a 4-fold signal enhancement in commercial rapid diagnostic tests (Figure 7). This study 99 demonstrated that optimizing the IMAC metal-ligand combination for a particular application is critical for efficient biomarker capture and elution; the initial binding cannot be too tight so as to prevent biomarker elution with a competing ligand (e.g., imidazole) nor too weak so as to attain suboptimal biomarker enrichment. 88,99…”
Section: Metal-based Sample Preparationmentioning
confidence: 98%
“…The authors found that Co 2+ and Zn 2+ exhibited the fastest binding kinetics (highest k on ) and the highest HRP2 binding affinity (lowest K D ) on BLI biosensors. 99 When the same IMAC complexes were incorporated into a loose solid phase resin, Zn(II)-NTA resulted in the fastest complete binding of HRP2 per mole of divalent metal while also allowing for the most efficient elution of HRP2 upon the addition of imidazole. Once a metal had been selected, HRP2’s binding and elution behavior was evaluated against a variety of ligands and solid supports.…”
Section: Metal-based Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of a successful non-incorporating large-scale use strategy for biopolymer protein immobilization is used in a type of affinity chromatography termed IMAC (immobilized metal affinity chromatography) [ 18 , 19 ]. IMAC uses agarose beads with grafted chelating moieties (iminodiacetic acid—IDA, nitrilotriacetic acid—NTA).…”
Section: Introductionmentioning
confidence: 99%